PENGARUH PAJANAN PARTIKEL KARBOFURAN TERHADAP KELUHAN SUBJEKTIF PEKERJA DI BAGIAN PRODUKSI PT PETROKIMIA KAYAKU GRESIK - Devisnaini Rahmah; Rachmaniyah .; Sri Mardoyo (GEMA LINGKUNGAN KESEHATAN, 2015)
PT Petrokimia Kayaku Gresik is a company engaged in the field of pesticides.  Its productionprocess is divided into several parts: liquid, powder (granules), solids and biological fertilizersproduction. The production process includes process of making Petrofur products that usecarbofuran raw material that cause dust resulting direct exposure to workers in production section.Identification toward characteristics of production worker showed that some workers did not wearpersonal protective equipment such as masks and gloves, therefore subjective complaints andhealth problems appeared. Research was conducted analytically with cross sectional approach. Dust was measured by usingHVDS and questionnaire to 30 people. This study used statistical test of "Chi Square" with α = 0.05to determine effect of carbofuran particle on subjective complaints of workers in productionsection.Result of the research showed that carbofuran particle level exceeded Ministry of Health TLV ofKepmenkes No.1405/Menkes/SK/XI/2002 by 0.09 and 0.07. After statistical test, there was no influence between the particles of carbofuran on subjective complaints of workers (p=0.080), work period (p=0.468), nevertheless, there was influence between age and subjective complaints(p=0.45).This study concludes that there was no effect of carbofuran particle level on subjective complaints.The company should pay attention on dust control technically, administratively and providepersonal protective equipment to prevent complaints and health problems in workers in productionsection.